Quantum Information and Computing : Waseda University, Tokyo, Japan 29-31 October 2003, Tokyo University of Science, Tokyo, Japan 1-3 November 2003, International Institute of Advanced Study, Kyoto, Japan 5-7 November 2003, Mei. - Accardi, Luigi; Ohya, Masanori; Watanabe, N. (World Scientific, 2006)
The main purpose of this volume is to emphasize the multidisciplinary aspects of this very active new line of research in which concrete technological and industrial realizations require the combined efforts of experimental and theoretical physicists, mathematicians and engineers.